Cultura digital e aprendizagens : a transcendência dos espaços instituídos na formação no ensino superior - Anjos, Rosana Abutakka Vasconcelos dos (2021)
ABSTRACT: Digital culture evokes us to reexamine many human activities in the different fields that make up society. This is the case of education, which, from the use of technologies, explores possibilities to re-signify its educational contexts as a way to monitor the activities of students in synergy with digital culture. This reality of intense use of technologies has been affecting the most conventional educational models, which perhaps implies new attitudes by the students themselves in conducting their learning process, which tends not to be restricted to the space of the classroom, but strengthen by the internet, due to the access and use of its multiple resources and materials. Therefore, the issue that arises is the understanding of how these organizations of learning occur, based on the exchange established between the classroom and cyberspace. Thus, this research aims to understand how the processes of formal learning of higher education students are organized based on the use of the most varied types of information and educational resources available on the internet. This study is based on the historical-cultural theory, by Lev Vygotsky (1996, 2007), as it understands the importance of interactions as practices for the construction of learning, as well as the relationship mediated by technologies, or technological mediation. With a qualitative approach, with the adoption of participant observation methodology, the research considered as locus 11 on-site undergraduate courses belonging to the Federal University of Mato Grosso. To this end, 2,373 e-mails were sent to students in these courses, with an effective response of 404 participants; 31 students were selected and participated in the semi-structured interview stage; from this amount, 15 participated in the observation stage, which made it possible to build their Learning Trails, which represent the path taken for the development of programmed activities of their course in the moments of study-learning, after classes. Therefore, the research did not measure students’ learning, but followed their itinerary in the construction of knowledge. Supported by historical-cultural theory, the research findings were analyzed, and revealed that students reorganize their learning processes, conceiving different learning ecologies from the use of the internet and its resources, such as videos, websites and digital texts. To a large extent, the interaction takes place by means of messaging applications and, consequently, the study practices are closely consolidated by the mediating relationship of the technologies. Thus, the results indicate that students overflow the classroom and transcend the content received by teachers. They go beyond, to cyberspace, which for them is an important space for their knowledge. Furthermore, it became evident that the virtual territories of young students are demarcated by the access and consumption of the services of large companies in the digital market. This makes reference to the importance of the instituted education being closer to the training of young students, in the perspective of proclaiming and practicing what we define as a critical digital culture.